The influence of different detection cycles on the detection results of HBsAg ELISA - DENG Yanqing; WAN Zhiting; HUANG Boquan; LIANG Haojian; DU Rongsong; LI Zhongping; ZHENG Jianting; XU Ru; WANG Min; WANG Hao (Zhongguo shuxue zazhi)
[Objective] To analyze the influence of the cycle length of hepatitis B surface antigen (HBsAg) double reagent positive samples collected from voluntary blood donors in Guangzhou on the detection results. [Methods] A total of 127 044 blood samples from voluntary blood donors at Guangzhou Blood Center from August 10 to December 9, 2023 were selected. Two ELISA reagents were used for HBsAg detection, and samples with HBsAg double reagent positive and S/CO values<10 were tested continuously for 7 days to observe the changes in their S/CO values. [Results] A total of 505 HBsAg double reagent positive samples were detected, of which 52 had S/CO values less than 10. After 7 consecutive days of uninterrupted testing, the S/CO values of Wantai (median 5 decreased to 3) and Xinchuang (median 5 decreased to 3) showed an overall downward trend, and the HBsAg missed detection rate showed an upward trend (from 0 on the first day to 1/10 000 on the seventh day). A total of 13 cases had negative double reagent test results within the 7-day testing cycle. [Conclusion] With the extension of the detection cycle, the S/CO value of HBsAg detection shows a downward trend, and the missed detection rate of HBsAg shows an upward trend. Samples used for HBsAg detection should be tested promptly after sampling to improve the quality of blood testing.